THE EFFECT OF 3H (Here, Hidden, and in my Head) STRATEGY ON STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT - Ika Nurkasih; Berlin Sibarani (Universitas Negeri Medan, 2016)
This study was intended to find out the effect of applying 3H (Here, Hidden, and in my Head) Strategy on students’ reading comprehension in narrative text. It was conducted by using experimental research design. The population of this study was the second year students of SMP Al Hidayah Medan. The sample of this research was two classes which consisted of experimental and control group which were chosen by using clustering technique. There were thirty students which were taken as the sample in each class. The experimental group was taught by 3H (Here, Hidden, and in my Head) Strategy while control group was taught without 3H (Here, Hidden, and in my Head) Strategy. The instrument of collecting the data was multiple choice test which consists of 20 items. To obtain the reliability of the test, the researcher used Kuder Richardson (KR 20) formula. The calculation showed that the reliability is 0.84 (very high). The data were analyzed by using t-test. The calculation showed that t-observed (5.2) was higher than t-table (2.00) at the level of significance (ơ) 0.05 with degree of freedom (df) 58. The result of this study showed that 3H (Here, Hidden, and in my Head) Strategy was significantly affect on students’ reading comprehension achievement.